2020
DOI: 10.1002/slct.202000336
|View full text |Cite
|
Sign up to set email alerts
|

Amine‐Terminated Ionic Liquid Modified Magnetic Graphene Oxide (MGO‐IL‐NH2): A Highly Efficient and Reusable Nanocatalyst for the Synthesis of 3‐Amino Alkylated Indoles

Abstract: Amine‐terminated ionic liquid has been covalently fabricated over the surface of Magnetic graphene oxide nanosheets. The structure of prepared material has been confirmed by various characterization techniques such as Fourier Transform Infrared Spectroscopy (FT‐IR), Powder XRD, Vibrating Sample Magnetometer (VSM), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), Energy Dispersive X‐ray spectroscopy (EDX). The prepared material demonstrates its supremacy as an efficient, recyclable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Additionally, the catalyst is retrieved using an external magnet, and a recyclability test revealed that the catalyst may be reused up to seven times without losing its catalytic efficiency (Scheme 23, Table 15). [31]…”
Section: One Nitrogen Containing Heteroatommentioning
confidence: 99%
“…Additionally, the catalyst is retrieved using an external magnet, and a recyclability test revealed that the catalyst may be reused up to seven times without losing its catalytic efficiency (Scheme 23, Table 15). [31]…”
Section: One Nitrogen Containing Heteroatommentioning
confidence: 99%
“…The resulting magnetic graphene oxide (MGO) was functionalized with imidazole by the reaction of MGO with 3-chloropropyltrimeth-oxysilane followed by N-alkylation of imidazolium salt. Finally, the quaternization of the resultant product was achieved by the reaction of the resultant with 2-chloroethylamine in order to obtain the final magnetic graphene oxide-supported amine-functionalized IL (MGO−IL−NH 2 ) ( Figure 1 ) [ 10 ].…”
Section: Application Of Ilsmentioning
confidence: 99%
“…One of the ways to change the functional properties of GO is covalent or non-covalent modification of GO [3][4][5], which is essential for the creation of various composite materials [6,7]. Interest in the derivatization of GO stems from the wide possibilities of regulating the chemical and physical properties of the material which are due to the addition of a certain amount of both organic functional groups on the basal plane and on the edge sections of GO and of inorganic compounds [8][9][10][11]. There has been growing interest in the modification of organic structures containing an amino group, especially aliphatic and/or aromatic amines, to change the structure of the GO surface [12][13][14].…”
Section: Introductionmentioning
confidence: 99%